Ṭarīqah Mubāsyarah dalam Pembelajaran Bahasa Arab: Kajian Literatur terhadap Konsep, Penerapan, dan Efektivitasnya - Nauwal Aufa; Mukhlisah (Jurnal Aktual Pendidikan Indonesia, 2026)
Arabic language instruction requires an appropriate method to ensure that learners not only grasp linguistic rules but also gain the ability to use the language in communication. One well-known approach is ṭarīqah mubāsyarah or the direct method which emphasizes the immediate use of Arabic during the learning process without relying on translation. This study aims to examine the concept, implementation, and effectiveness of ṭarīqah mubāsyarah in Arabic language instruction through a literature review. The research employs a library research methodology, analyzing various scholarly sources such as journals and books related to the direct method. The findings indicate that ṭarīqah mubāsyarah plays a role in enhancing learners' communication skills, particularly in speaking and listening. However, its implementation faces certain challenges, such as the requirement for teachers to possess adequate Arabic proficiency and the need to adapt the method to the learners' specific circumstances. Thus, ṭarīqah mubāsyarah serves as an effective alternative method for teaching Arabic, provided it is implemented in alignment with learning objectives and needs.